PEMBUATAN WEBSITE SEKOLAH MENENGAH PERTAMA (SMP) NEGERI 12 SELUMA - Sapri Sapri; Feri Hari Utami (Jurnal Media Infotama, 2011)
Developments in science and technology developed in line with the progress of time which can support activities undertaken by humans. Computer is a human creation, combined with science to develop in accordance with user needs.Website Creation SMP Negeri 12 Seluma menngunakan Adobe Dreamweaver CS.4 (2013).Tempat and Research Forum Time At SMP Negeri 12 Seluma, etode peneltitan is used in the method of observation, and interviews, the existing problems in junior high is still menngunakan Seluma 12 Board announcement, speaking from mouth to mouth in informing and still less efficient and abstract This study aims to create a website junior high school (SMP) State of science and technology development in line with the progress of time to support the activities of 12 Seluma CS.4 using Macromedia Dreamweaver. This research is done for 5 month, the method used in this study is the use of data collection methods such as: methods of observation, interviews, and Stadi library. Applications used in the manufacture of SMP Negeri 12 Seluma website using Macromedia Dreamweaver CS.4, and language programs used are PHP programming and MySQL as the database that supports this application. From the results of this study indicate that the website is very useful to reduce the lack of information about the school SMP Negeri 12 Seluma and within a certain time, so it does not necessarily have to come to a place of SMP Negeri 12 Seluma to get what is needed. Website SMP Negeri 12 Seluma should go online so that can be accessed anytime, anywhere, and by anyone and certainly through computers connected to the internet.